Human communication : - DeVito, Joseph A. (Pearson, 2009)
The book surveys the broad field of human communication, giving attention to theory, research, and skill development. This Eleventh Edition provides an in-depth look at the concepts and principles of human communication, emphasizing public speaking, interpersonal communication, and small group communication. Designed to allow flexibility in teaching approaches, Human Communication: The Basic Course offers instructors a wide range of topics to discuss and apply to real-world experiences